In vitro Dissolution Testing and Pharmacokinetic Studies of Silymarin Solid Dispersion After Oral Administration to Healthy Pigs - Xu, Ying; Li, Jie; He, Bing; Feng, Tingsong; Liang, Lijie; Huang, Xianhui (Frontiers in Veterinary Science, 2022)
We evaluated the pharmacokinetics of silymarin solid dispersion in pigs to determine whether silybin bioavailability would be increased over that of a silymarin premix. In vitro dissolution testing was conducted using dissolution apparatus 1 (baskets) at 100 rpm at 37±0.5℃ in pH 1.2 HCl, pH 6.8 phosphate and pH 4.3 acetate buffers containing 0.5% Tween-80. In vivo pharmacokinetics were studied using 16 healthy pigs (Yorkshire × Landrace) that were randomly assigned to 2 groups. Silymarin as solid dispersion and premix dosage forms were administered directly by stomach tubes at 50 mg kg-1 silybin. In vitro dissolution of silybin for the premix was 35.02, 35.90 and 38.70% in these buffers, respectively. In contrast, silybin dissolution in solid dispersions was increased to 82.92, 87.48 and 99.70%, respectively. Silymarin solid dispersion administered at a single dose resulted a peak concentration (Cmax) of 1190.02 ± 246.97 ng mL-1 with the area under the curve (AUC0－∞) at 1299.19 ± 67.61 ng mL-1h-1. These parameters for the premix groups were 411.35 ± 84.92 ng mL-1 and 569.98 ± 166.28 ng mL-1h-1, respectively. The Cmax and AUC0－∞ values for the solid dispersion were about twice that of the premix and were consistent with the in vitro dissolution data.